Frequency of high-risk genotypes of human papilloma virus in oral lesions. - Martha Rebolledo-Cobos; Luz Quintero; Tatiana Echeverría; José Ángel Pertúz; Alfonso Bettin (Universidad de Concepción., 2020)
Some genotypes of the human papilloma virus (HPV) in the oral cavity cause genetic instability that may lead to cancer. Clinical and histological diagnoses are key tools; however, molecular techniques allow predicting, detecting and monitoring the disease. Objective: To identify the frequency of four high-risk HPV genotypes and their association with lesions in the oral cavity. Materials and Methods: Descriptive cross-sectional study with a sample of 48 patients diagnosed with hyperplastic lesions and others currently classified as potentially malignant disorders (PMDs) of the oral cavity, who underwent biopsies, histopathological analysis, and HPV16, 18, 31, and 45 detection and genotyping by polymerase chain reaction (PCR). Results: Epithelial hyperplasia was the most frequent lesion found in 45.8% (n=22) of patients. Nicotine palatinus and leukoplakia were found in 8.3% and 6.2%, respectively; oral cancer in 6.2%. The total frequency of HPV was 12.5% (6/48). Oral papilloma was found in 6.1% (3/48), and nicotine palatinus and oral cancer in 2.0% each (1/48). HPV16, HPV31, and HPV45 were detected, while HPV18 was not observed. HPV16 was the most frequent genotype found (4 out of 6 patients), while HPV31 and HPV45 were found in one patient each. Only one genotype per lesion was found. The presence of HPV was associated with lesions (χ2=11.810; p=0.0375). No significant association with age and gender was found. Conclusion: High-risk HPV continues to be present in oral lesions. The HPV16 viral genotype was the most frequent in the studied lesions.